Biochemical Composition and Alkaline Extraction Optimization of Soluble Bioactive Compounds from the Green Algae Caulerpa cylindraceae - Tahar, Amani; Zghida, Haïfa; Pereira, Débora Tomazi; Korbee-Peinado, Nathalie; Treichel, Helen; López-Figueroa, Félix; Achour, Lotfi (MDPI, 2025)
There is a growing interest in studying the bioactive compounds of invasive green macroalga Caulerpa cylindracea due to their potential biotechnological applications. Algal samples were collected from two sites and seasons. Elemental analysis showed the abundance of carbon in the raw material as a source of carbohydrates. The total protein content in different samples ranged from 8.17 to 9.98%. Total lipids in different samples were around 2%. Fatty acid (FA) results revealed the presence of various types, including omega-3 and omega-6 PUFA. Furthermore, an alkaline hydrolysis optimization using response surface methodology was investigated to extract soluble compounds. It showed that the best combination for polyphenols and ABTS was 12.5% sodium carbonate (SC) at 100 °C for 8 h; however, the best combination for proteins and carbohydrates was 7.5% SC at 100 °C for 5 h. A combination of ultrasound pretreatments was carried out to assess the enhancement of the contents. Thus, an increasing amount was recorded for polyphenols and antioxidant capacity. Ultrasound pretreatment results in decreasing extraction time for all compounds. Results showed that the invasive seaweeds, causing environmental impacts in the Mediterranean Sea, represent an interesting source of bioactive compounds.
Keywords: Algas; Alkaline hydrolysis; Bioactive compounds; Caulerpa cylindracea;; Fatty acid; Ultrasound-assisted extraction